1984
DOI: 10.1111/j.1365-2311.1984.tb00839.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenology of weight, moisture and energy reserves of Australian monarch butterflies, Danaus plexippus

Abstract: 1. In the Sydney area of New South Wales, dry weights of reproductive monarch butterflies averaged 156 mg and were higher during winter than in other seasons. Dry weights of non-reproductive monarchs ranged from 216 t o 324 mg and declined by 1~2 5 % during overwintering.2. Fat in reproductive butterflies ranged from 0.009 to 0.017g/O.lg dry weight and was lower during winter than in other seasons. Fat content of nonreproductive monarchs washigher (0.019-0.037 g/O.1 g) and declined by 24-51% during overwinteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…The high levels of abdominal lipid in newly emerged S. exempta, supported by ultrastructural evidence (A. Gunn, unpublished results), show that like other Lepidoptera such as Prodenia eridiana (Stevenson, 1968(Stevenson, ,1969 grandiosella (Chippendale, 1971), Danaus plexipus (Cenedella, 1971;Brown & Chippendale, 1974;James, 1984), S.exempta accumulates large quantities of lipid reserves during the larval stage which are held, probably as triglycerides, in the fat body (at emergence the oocytes are immature and constitute a small proportion of the abdominal lipid as well as protein and carbohydrate). As in P.eridiana (Stevenson, 1968), glycogen is present in only small quantities.…”
Section: Discussionmentioning
confidence: 71%
“…The high levels of abdominal lipid in newly emerged S. exempta, supported by ultrastructural evidence (A. Gunn, unpublished results), show that like other Lepidoptera such as Prodenia eridiana (Stevenson, 1968(Stevenson, ,1969 grandiosella (Chippendale, 1971), Danaus plexipus (Cenedella, 1971;Brown & Chippendale, 1974;James, 1984), S.exempta accumulates large quantities of lipid reserves during the larval stage which are held, probably as triglycerides, in the fat body (at emergence the oocytes are immature and constitute a small proportion of the abdominal lipid as well as protein and carbohydrate). As in P.eridiana (Stevenson, 1968), glycogen is present in only small quantities.…”
Section: Discussionmentioning
confidence: 71%
“…The lipid content of freshly eclosed monarchs was similar to previous studies in which monarchs were collected in the field and reared in the laboratory (Beall 1948, Cohen 1985, James 1984, Brower et al 2006, Brower et al 2015.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, Renault et al (2003) found survival at cold but non-lethal temperatures was positively correlated with insect body size in Alphitobius diaperinus (Coleoptera: Tenebrionidae), and larger insects lost weight at a slower rate than smaller ones. Overwintering can require a high proportion of pre-winter lipid reserves with death occurring in insects in which lipid levels drop to low levels (Alonso-Mejía et al, 1997;James, 1984). In NZ, larger heather beetles collected from the field at the start of winter have a higher proportion of their body weight as lipids than smaller beetles.…”
Section: Discussionmentioning
confidence: 99%